Teriflunomide treatment reduces B cells in patients with MS. Issue 6 (November 2017) - Gandoglia, Ilaria; Ivaldi, Federico; Laroni, Alice; Benvenuto, Federica; Solaro, Claudio; Mancardi, Gianluigi; Kerlero de Rosbo, Nicole; Uccelli, Antonio
Abstract : Objective: To study the immunomodulatory effect of teriflunomide on innate and adaptive immune cell populations through a pilot, open-label, observational study in a cohort of patients with relapsing-remitting MS. Methods: Blood lymphocytes were isolated from 10 patients with MS before and after 3 or 12 months of treatment. Adaptive and innate immune cell subsets were analyzed by flow cytometry as follows: B cells (memory, regulatory, and mature subsets), T cells (effector and regulatory subsets), and natural killer (NK) cells (CD56 dim and CD56 bright subsets). Results: Our results show that teriflunomide significantly reduces absolute counts of total CD19 + B cells and mature and regulatory B-cell subsets. T cells were affected to a lesser extent, with a trend in reduction of absolute counts for both T effector CD4 + cells (Th1, Th17 and Th1/17) and T regulatory CD8 + and CD4 + cells. Teriflunomide had no detectable effect on NK-cell numbers. Conclusions: In our small cohort, teriflunomide treatment affects mainly and significantly on B-cell numbers, while having a milder effect on T-cell numbers. Larger cohorts are necessary to confirm these findings and understand the effect of teriflunomide on the functionality of these cells.